THE EFFECT OF MANAGERIAL OWNERSHIP AND INSTITUTIONAL OWNERSHIP ON COMPANY FINANCIAL PERFORMANCE - Altania, Shendy; Tanno, Aries (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
Managerial and institutional ownership within companies is becoming increasingly important and commonplace in today's modern era. Therefore, this research investigated the effect of managerial and institutional ownership on the company's financial performance. The method used in this research is a quantitative approach. This research uses a secondary research approach with research objects in the form of manufacturing companies listed on the Indonesia Stock Exchange in the 2017-2021 period. The results of this study indicate that managerial ownership significantly influences the company's financial performance. This is supported by a significance value of 0.000, less than 0.05. Managerial ownership can have a significant positive impact on a company's financial performance because it can increase management's motivation to work harder and pay more attention to the company's long-term performance so that it can provide benefits to the company and shareholders. In addition, the results of this study also show that institutional ownership significantly influences the company's financial performance, indicated by a significance value of 0.025, less than 0.05. Institutional ownership can increase oversight of company management, provide positive signals to the market, and help companies to obtain greater resources.